Method for analysis of surface molecule alteration upon phagocytosis by flow cytometry - Singboottra P. (2014)
In this study, we introduce an application of flow cytometry for the concurrent detection of phagocytotic cells and surface molecules involved in the phagocytic process. E. coli expressing green fluorescent protein (GFP) were applied as the phagocytosable particles. Blood samples were incubated with E. coli expressing GFP, followed by indirect immunofluorescence using four candidate monoclonal antibodies (mAbs). Granulocytes that had phagocytosed E. coli exhibited high levels of GFP intensity, in contrast to the nonphagocytosed cells. By comparing the level of expression of molecules expressed on phagocytosed granulocytes with that of non-phagocytosed cells by flow cytometry, it enabled the determination of the expression and alteration of the cell surface molecules upon phogocytosis. Of the four mAbs used in this study, upon phagocytosis, molecules recognized by mAbs WK13, COSA5A and COSA33NL were up-regulated. However, CD15 recognized by mAb VIMD5 was down-regulated. The proposed method will benefit the study of phagocytic mechanisms in the future.